2000
DOI: 10.1086/302955
|View full text |Cite
|
Sign up to set email alerts
|

Aicardi-Goutières Syndrome Displays Genetic Heterogeneity with One Locus (AGS1) on Chromosome 3p21

Abstract: We have studied 23 children from 13 families with a clinical diagnosis of Aicardi-Goutières syndrome. Affected individuals had developed an early-onset progressive encephalopathy that was characterized by a normal head circumference at birth, basal ganglia calcification, negative viral studies, and abnormalities of cerebrospinal fluid comprising either raised white cell counts and/or raised levels of interferon-alpha. By means of genomewide linkage analysis, a maximum-heterogeneity LOD score of 5.28 was reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 33 publications
1
56
0
5
Order By: Relevance
“…Clarification of the genetic basis of AGS and expansion of the AGS phenotype [Stephenson et al, 1997;Crow et al, 2000Crow et al, , 2003Sanchis et al, 2005;Rice et al, 2007] suggests that this distinction is not appropriate so that the previous OMIM entry for pseudo-TORCH syndrome (251290) has been withdrawn and moved to the AGS (225750) entry. However, we note that a number of other congenital infection-like phenotypes, obviously distinct from AGS, have also been described [e.g., Slee et al, 1999;Vivarelli et al, 2001;Knoblauch et al, 2003;Gardner et al, 2005;Watts et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Clarification of the genetic basis of AGS and expansion of the AGS phenotype [Stephenson et al, 1997;Crow et al, 2000Crow et al, , 2003Sanchis et al, 2005;Rice et al, 2007] suggests that this distinction is not appropriate so that the previous OMIM entry for pseudo-TORCH syndrome (251290) has been withdrawn and moved to the AGS (225750) entry. However, we note that a number of other congenital infection-like phenotypes, obviously distinct from AGS, have also been described [e.g., Slee et al, 1999;Vivarelli et al, 2001;Knoblauch et al, 2003;Gardner et al, 2005;Watts et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Due to common clinical features, a common genetic origin has been considered for CRV, HRV and HERNS, and recently all these syndromes have been linked to the same locus on chromosome 3p21 [17]. Interestingly, the AicardiGoutieres syndrome, a further disease with progressive leukoencephalopathy, has been located to 3p21 [2], a region to which also the polyglutamine disease spinocerebellar ataxia 7 has been linked. We screened for polyglutamine proteins in one patient.…”
Section: ■ Pathology and Mechanisms Of Disease Progressionmentioning
confidence: 99%
“…Moreover, IFN-α levels were higher in CSF than in serum, which suggested an intrathecal synthesis of this antiviral cytokine, but also that it could play a role in the pathogenesis of this encephalopathy [3,4]. These authors concluded that their study revealed that the syndrome was inherited in an autosomal recessive manner, a conclusion also suggested by previous and further reports [2][3][4][5][6][7][8][9][10][11][12][13][14]. Interestingly, studies in sibs demonstrated that AGS may course with a highly variable phenotype [9,11,12], which suggests that different genes or the existence of different mutations in a single gene may be responsible for the appearance or the evolution of the AGS.…”
Section: Introductionmentioning
confidence: 64%
“…Since then, mutations in several genes leading to the apparition of interferon signature have been implicated in this syndrome [13][14][15][16][17]44]; however it was not until 2014 that mutations in the IFIH1 gene were involved in the etiopathogeny of AGS [45,46], demonstrating that IFIH1 mutations led to an increase in the production of type 1 interferon and to an increased transription of genes stimulated by this cytokine. Interestingly, in the last of these studies it was shown that all the patients with IFIH1 mutations presented autoantibodies, which suggested that these mutations contributed to the presentation of autoinmune phenotypes [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation